PENGARUH KEMAMPUAN MEMBACA AL-QUR’AN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VII E DI MTs 2 KUANTAN SINGINGI - Upipa Aselta; Andrizal Andrizal; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2023)
This research is motivated by independent learning in class IXc at MTs N Kuantan Singingi. In this research on student learning independence, the IXc class which consists of 32 students. Studens learning independence is of course very important for students so that students better understand the learning material delivered by the teacher event though there are disturbances during in the learning process. This study aims to determine independent learning in Al-Qur'an Hadith Learning in Class IXc at MTs N 2 Kuantan Singingi. This type of research is qualitative, the population of this research is all class IX which consists of 4 classes which open 130 students while the sample of this study opens 32 people.Data collection techniques used in this study were observation, interviews and documentation. From the results of the data analysis that the researchers conducted in class IXc and the results of interviews from the Al-Quran Hadith subject teacher at MTs N 2 Kuantan Singingi, it can be said that independent learning in class XIc is quite good. This can be seen from the data Learning Model Flipped Classroom method with the help of lectures in class, in this activity the application showed 910 learning outcomes with an average of 69.63, students who did not complete 5, students who completed there 8 and the completeness score is analysis which shows that students are confident when answering questions from the teacher, collecting assignments according to the set time, asking if they do not understand the material, do assignments independently without cheating on their friends, study outside school hours with friends, study anywhere and look for other learning resources such as books and searching material on Google